Significance of Pretreatment Neutrophil-to-Lymphocyte Ratio in Mucoepidermoid Carcinoma of Pediatrics: A Multicenter Study - Gao, Hua; Gao, Qing; Sun, Jinlan (Frontiers in Pediatrics, 2020)
Background: Our goal was to analyze the value of the pretreatment neutrophil-to-lymphocyte ratio (NLR) in the prognosis of pediatrics with parotid mucoepidermoid carcinoma (MEC). Methods: Patients (≤ 18 years old) undergoing surgical treatment for primary parotid MEC were enrolled from multiple clinical centers retrospectively. The χ2-test was used to analyze the associations between clinicopathological variables and the NLR. The main study endpoints were recurrence-free survival (RFS) and disease-specific survival (DSS). The prognostic value of NLR was assessed by Kaplan–Meier method and Cox model analysis. Results: There were 88 patients included in total, with mean NLR of 2.32 (range, 1.8–6.0). Histologic tumor grade and tumor stage were associated with the NLR significantly. The 10-year RFS rates were 98 and 81% for patients with an NLR < 2.32 and patients with an NLR ≥ 2.32, respectively, the difference was significant (p = 0.010). The 10-year DSS rate was 97 and 81% for patients with an NLR < 2.32 and patients with an NLR ≥ 2.32, respectively; the difference was not significant (p = 0.072). The independence of NLR in predicting the RFS was further confirmed in Cox model analysis. Conclusion: The NLR significantly affects the prognosis in pediatrics with primary parotid MEC.